(untitled) (Informatica, 2023)
For learning environments like schools and colleges, predicting the performance of students is one of the most crucial topics since it aids in the creation of practical systems that, among other things, promote academic performance and prevent dropouts. The decision-makers and stakeholders in educational institutions always seek tools that help in predicting the number of failed courses for the students. These tools can help in finding and investigating the factors that led to this failure. In this paper, many supervised machine learning algorithms will investigate finding and exploring the optimal algorithm for predicting the number of failed courses of students. An imbalanced dataset will be handled with Synthetic Minority Oversampling TEchinque (SMOTE) to get an equal representation of the final class. Two feature selection approaches will be implemented to find the best approach that produces a highly accurate prediction. Wrapper with Particle Swarm Optimization (SPO) will be applied to find the optimal subset of features, and Info Gain with ranker to get the most correlated individual features to the final class. Many supervised algorithms will be implemented such as (Naïve Bayes, Random Forest, Random Tree, C4.5, LMT, Logistic, and Sequential Minimal Optimization algorithm (SMO)). The findings show that the wrapper filter with SPO-based SMOTE outperforms the Info-Gain filter with SMOTE and improves the performance of the algorithms. Random Forest outperforms the other supervised machine learning algorithms with (85.6%) in TP average rate and Recall, and (96.7%) in ROC curve.